(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This article explores the importance and role of effective time management in learning English. It addresses common issues faced in the language learning process, offers suggestions and solutions for time management, reviews expert opinions and experiences in this field, and discusses the expected outcomes in the future. The article provides an innovative approach, combining personal insights and examples.